2018
DOI: 10.1002/eat.22828
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness patterns as state biomarker of anorexia nervosa

Abstract: Higher cortical thickness in medial orbitofrontal cortex and insula probably contributes to higher gray matter volume in AN in those regions. The machine-learning algorithm identified a mixed pattern of mostly higher orbital and insular, but relatively lower superior frontal cortical thickness in individuals with current AN. These novel results suggest that regional cortical thickness patterns could be state markers for AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 60 publications
2
59
3
Order By: Relevance
“…Our results of cortical thinning in different regions in acute AN patients align with several previous studies (Bär et al, ; Bernardoni et al, ; Fuglset et al, , ; King et al, ). However, Lavagnino et al () reported no significant cortical thinning, and in a later study, they found both regional cortical thinning in frontal areas and thickening in insular and orbitofrontal cortices in AN and REC cases (Lavagnino et al, ). These discrepancies might be due to different methodologies (FreeSurfer) (Lavagnino et al, , ) or shorter duration of illness (Lavagnino et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our results of cortical thinning in different regions in acute AN patients align with several previous studies (Bär et al, ; Bernardoni et al, ; Fuglset et al, , ; King et al, ). However, Lavagnino et al () reported no significant cortical thinning, and in a later study, they found both regional cortical thinning in frontal areas and thickening in insular and orbitofrontal cortices in AN and REC cases (Lavagnino et al, ). These discrepancies might be due to different methodologies (FreeSurfer) (Lavagnino et al, , ) or shorter duration of illness (Lavagnino et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Cortical thickness, therefore, is unlikely to represent a permanent trait marker or scar (King et al, 2015). According to previous studies, cortical thinning appears widespread across the brain, focused on the frontal regions (Bär et al, 2015;Fuglset et al, 2016;Lavagnino et al, 2018). Cortical thinning in prefrontal brain areas could contribute to altered response inhibition (Oberndorfer, Kaye, Simmons, Strigo, & Matthews, 2011;Wierenga et al, 2014) and set shifting (Sato et al, 2013) in AN.…”
Section: Cortical Thicknessmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent reports are in support of those findings. Studies by Nickel et al (2018) and Bang, Ro, and Endestad (2018) found normal cortical volume and thickness and indication of normal white matter after recovery from anorexia nervosa, and a study by Lavagnino et al (2018) suggests that altered cortical thickness is rather a state than trait marker in anorexia nervosa. Atypical anorexia nervosa is defined as anorexia nervosa that does not meet full diagnostic criteria, typically those individuals are not below a certain weight threshold, such as the 5th percentile for age adjusted BMI.…”
Section: Research On Brain Structurementioning
confidence: 98%